Thinking Process of Student in Solving Mathematical Problems Based on Logis-Mathematical Intelligence - Purjiyo Purjiyo; Imam Sujadi; Diari Indriati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The root of the problem of this research is the lack of interest in student learning during the COVID-19 pandemic which resulted in low student learning outcomes. The purpose of this study was to see the improvement of student learning outcomes during online learning by using learning videos on a two-variable linear equation system material. The type of research used in this research is classroom action research which was carried out at MTS Negeri 1 Simalungun. This research was conducted in two cycles with each action including planning, implementing, observing and reflecting. To see the learning outcomes used tests in cycles I and II. The results of the study show that learning video media on the material of a two-variable linear equation system in the Covid-19 Pandemic Era can improve learning outcomes and minimum learning mastery of students in class VIII-5 MTS Negeri 1 Simalungun for the 2020/2021 academic year". The completeness of student learning outcomes on the SPLDV material after being taught using learning video media when the initial condition (23.52%) increased to 52.94%. Furthermore, there was an increase in student learning outcomes by 23.53% with a mastery level of learning obtained around 76.47%. This result is in line with what is expected, namely 75% of students complete.